Unraveling the impact of sediment size distribution on flow-sediment hysteresis in estuarine environments: insights from size-resolved sediment transport modeling - Fang, Zheng; Xu, Fanghua; Zhang, Xueyang (Environmental Research Communications, 2025)
Flow-sediment hysteresis, a nonlinear time-lagged relationship between sediment transport and hydrodynamic conditions, is particularly important yet difficult to simulate in tidal estuarine environments. This study introduces a size-resolved sediment transport model to simulate flow-sediment hysteresis, with an application in the Hudson River estuary. By incorporating variations in sediment size distribution induced by flocculation, the model allows for a more accurate simulation of flow-sediment hysteresis compared to traditional size-fixed models, achieving accuracy improvements of 4.89% ∼ 12.19% during tidal cycles. Moreover, budget analyses and correlation matrix analyses are conducted. The results indicate that the dynamics of small and large flocs influence hysteresis differentially: flocculation processes dominate the behavior of small flocs, while settling and vertical diffusion processes primarily affect large flocs. These insights offer a deeper understanding of sediment transport in tidal estuaries, providing a robust framework for enhanced predictive modeling which can be adapted to other estuarine environments.